Kontribusi Power Otot Kontribusi Power Otot Lengan terhadapat Hasil Lempar Cakram Siswa Ekstrakurikuler SMA Negeri 1 Salo Kabupaten Kampar Siswa Ekstrakurikuler SMA Negeri 1 Salo Kabupaten Kampar - Sadikin, Ikhlas (INSPIREE: Indonesian Sport Innovation Review, 2021)
The  purpose  of  the study. The purpose of this study was to determine the contribution of arm muscle power to the results of discus throwing at SMA Negeri 1 Salo, Kampar Regency. Materials and methods. The form of this research is correlation research with the population of all extracurricular students of SMA Negeri 1 Salo, Kampar Regency with a total sample of 20 people. The sample in this study was obtained based on the total sampling technique. The instruments used in this study were arm muscle power tests and discus throwing results. Results. The results of data analysis in this study obtained an r count of 0.866 with a large contribution of 74.99%. This is classified as very good. Where obtained r arithmetic = 0.866>rtable= 0.444 with a contribution of 74.99% Conclusions. Based on the data analysis that has been done, it can be concluded that this study has a contribution of Arm Muscle Power (X) to the results of Discus Throwing (Y) extracurricular students of SMAN 1 Salo, Kampar Regency. Where r count 0.866>rtable 0.444, and there is a very strong contribution of arm muscle power to the discus throwing results of extracurricular students of SMA Negeri 1 Salo, Kampar Regency which is very strong, which is 74.99%, the remaining 25.01% is determined by other factors.